Hypertension due to renal artery stenosis - Husein Albar; Haeriah Rahman; Syarifuddin Rauf (Paediatrica Indonesiana, 2001)
A case of a 12-year-old boy with renal artery stenosis as a cause of hypertension is presented. The diagnosis of renal artery stenosis was established based on the bruit heard over costovertebral angle and the increased plasma rennin secretion, and further confirmed by angiogram finding. The detection of bruit, either on the abdomen or costovertebral angle, in association Indones with hypertension should initially lead to the consideration of the presence of renal artery stenosis.